Desafios e oportunidades das alianzas mercadologicas na cadeia produtiva da carne bovina - Ospina Patino, Harold; Dutra de Barcellos, Marcia; Furtado Velloso, Fernando; Angel Cardona, Juan C. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary The industry for the production and marketing of beef made profound changes in the last decade is looking to adapt the demands of the two largest consumer markets: competitiveness and quality of product. In part these changes were a consequence of health problems occurring in some countries, which generated significant changes in the size of the allocated quota to countries traditionally supplying the international market which have as their main challenge to maintain/increase the quota market gained due to the strong pressure by competing countries. In spite of health criteria and customs play an important role in determining the international marketing of beef the countries that have the largest volumes of trade that have competitive advantages (scale of production, abundance of land and work cheap, production systems in grazing with a strong investment in research and technology transfer) in their production systems that allow to market beef at low prices. However, the price is no longer the sole criterion considered in the international marketing of meat. Today consumers choose the products thinking on food safety, quality standards, the uniformity of the product and the environmental impact resulting from the generation of products. Thus the great challenge in the short term is to make sure the meat to be bought not to be sold, incorporating all the features in this sale inherent in the system of production. Therefore the search for more favorable markets need to identify, understand and manipulate clearly the critical points of control, mainly in marketing, considered the end of the production chain.